Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1128/jvi.67.4.2209-2220.1993
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus-induced genes: first lymphocyte-specific G protein-coupled peptide receptors

Abstract: Since Epstein-Barr virus (EBV) infection of Burkitt's lymphoma (BL) cells in vitro reproduces many of the activation effects of EBV infection of primary B lymphocytes, mRNAs induced in BL cells have been cloned and identified by subtractive hybridization. Nine genes encode RNAs which are 4-to >100-fold more abundant after EBV infection. Two of these, the genes for CD21 and vimentin, were previously known to be induced by EBV infection. Five others, the genes for cathepsin H, annexin VI (p68), serglycin proteog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
120
0
6

Year Published

1995
1995
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(139 citation statements)
references
References 88 publications
8
120
0
6
Order By: Relevance
“…Although the balanced actions of CCR7, CXCR4, and CXCR5 can explain much about the directed movement of B cells during T-dependent responses, it is more difficult to explain phenomena such as the localization of responding B cells into GCs (88) suggesting that perhaps other chemotactic receptors may also be involved in regulating B-cell migration. CCR7 was initially named Epstein-Barr virus induced 1 (EBI1) by virtue of the fact that it's mRNA was a greatly upregulated in Epstein-Barr virus-infected B cells (89). It is usually forgotten that this same study identified an mRNA encoding a second 7-transmembrane receptor, EBI2, which was similarly upregulated by Epstein-Barr virus infection (89).…”
Section: Ebi2 Controls Early B-cell Migration and Differentiationmentioning
confidence: 99%
“…Although the balanced actions of CCR7, CXCR4, and CXCR5 can explain much about the directed movement of B cells during T-dependent responses, it is more difficult to explain phenomena such as the localization of responding B cells into GCs (88) suggesting that perhaps other chemotactic receptors may also be involved in regulating B-cell migration. CCR7 was initially named Epstein-Barr virus induced 1 (EBI1) by virtue of the fact that it's mRNA was a greatly upregulated in Epstein-Barr virus-infected B cells (89). It is usually forgotten that this same study identified an mRNA encoding a second 7-transmembrane receptor, EBI2, which was similarly upregulated by Epstein-Barr virus infection (89).…”
Section: Ebi2 Controls Early B-cell Migration and Differentiationmentioning
confidence: 99%
“…T he G protein-coupled receptor (GPCR), EBI2 (Epstein-Barr virus (EBV)-induced gene 2, aka GPR183) is highly expressed in immune cells and activated by oxysterols (Birkenbach et al, 1993;Hannedouche et al, 2011;Liu et al, 2011). EBI2 signals through the pertussis toxin (PTx)-sensitive heterotrimeric G proteins of the Gi/o family leading to a decrease in cAMP production, calcium mobilization, and stimulation of the extracellular-signal-regulated kinase (ERK) pathway (Benned-Jensen et al, 2013;Gatto et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in B cells identified the gene for the Epstein-Barr virus-induced molecule 2 (EBI2), a member of the G-protein-coupled receptor (GPCR) family (8). EBI2 mRNA is detected constitutively in naive B cells, and its level increases after activation (6,9,10).…”
mentioning
confidence: 99%